2009
DOI: 10.1016/s1607-551x(09)70529-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Peripheral Arterial Stiffness in Patients With Chronic Kidney Disease in Southern Taiwan

Abstract: High prevalences of peripheral artery occlusive disease (PAOD) and increased arterial stiffness have been reported in patients with chronic kidney disease (CKD). However, these have not been assessed in Taiwan where the prevalence of CKD is high. The aim of this study was to investigate the determinants of PAOD and arterial stiffness in patients with CKD in southern Taiwan. We enrolled 169 patients with stage 3-5 CKD in one regional hospital. Ankle-brachial index (ABI) and brachial-ankle pulse wave velocity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Increased arterial stiffness was reported to be associated with decreased eGFR in cross-sectional studies. 19 Three longitudinal studies using different measurement methods of arterial stiffness (that is, augmentation index, radial-dorsalis pedis PWVs and aortic PWVs) showed that increased arterial stiffness was an independent predictor of renal function progression in patients with chronic kidney disease. [5][6][7] They explained their finding citing the greater transmission of elevated systemic blood pressure to the glomerular capillaries, thereby exacerbating glomerular hypertension caused by increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial stiffness was reported to be associated with decreased eGFR in cross-sectional studies. 19 Three longitudinal studies using different measurement methods of arterial stiffness (that is, augmentation index, radial-dorsalis pedis PWVs and aortic PWVs) showed that increased arterial stiffness was an independent predictor of renal function progression in patients with chronic kidney disease. [5][6][7] They explained their finding citing the greater transmission of elevated systemic blood pressure to the glomerular capillaries, thereby exacerbating glomerular hypertension caused by increased arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The ABI and brachial-ankle PWV were measured using an ABI-form device, which automatically and simultaneously measured BPs in both arms and ankles using an oscillometric method (10)(11)(12)(13)(14)(15)(16). Occlusion and monitoring cuffs were placed tightly around the upper arm without blood access and both sides of the lower extremities in the supine position.…”
Section: Assessment Of Abi and Brachial-ankle Pulse Wave Velocitymentioning
confidence: 99%
“…The ABI and brachial-ankle PWV measurements were done once in each patient. Because the ABI and brachial-ankle PWV were noninvasive and reliable diagnostic tools for peripheral vascular disease (11,13), patients with ABI ,0.9 or increased brachial-ankle PWV were considered to have peripheral vascular disease in this study.…”
Section: Assessment Of Abi and Brachial-ankle Pulse Wave Velocitymentioning
confidence: 99%
“…Increased arterial stiffness may be responsible for cardiovascular burden in the CKD population (3,4). Previous studies have reported the association between decreased estimated GFR (eGFR) and increased arterial stiffness (5)(6)(7). Decreased eGFR may predispose to increased arterial stiffness with multiple pathogenic mechanisms involved, including deranged calcium/phosphate balance, secondary hyperparathyroidism, homocysteine, lipoprotein(a) metabolism, fluid overload, alterations in the angiotensin and endothelin systems, malnutrition, uremic toxins, oxidative stress, insulin resistance, and alterations in inflammatory and coagulation pathways (8,9).…”
Section: Introductionmentioning
confidence: 99%